2015
DOI: 10.1016/j.bone.2015.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Role of IGF-I signaling in muscle bone interactions

Abstract: Skeletal muscle and bone rely on a number of growth factors to undergo development, modulate growth, and maintain physiological strength. A major player in these actions is insulin-like growth factor I (IGF-I). However, because this growth factor can directly enhance muscle mass and bone density, it alters the state of the musculoskeletal system indirectly through mechanical crosstalk between these two organ systems. Thus, there are clearly synergistic actions of IGF-I that extend beyond the direct activity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 153 publications
(147 reference statements)
1
88
0
7
Order By: Relevance
“…Bearing in mind the above, our data suggesting an overexpression of IGF-1Ec by injured tissues, such as by the surrounding tissues in prostate cancer, is reminiscent of the preferential expression of IGF-1Ec post-skeletal muscle damage and that of the myocardium during the post-infarction period. [30][31][32][33][34][35][36] Interestingly, species-specific differences of hEc and mE actions may point to a possible different mode of actions at the receptor level. It has been reported that mE requires IGF-1R for its bioactivity, 36 while hEc appears to act in an IGF-1R independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind the above, our data suggesting an overexpression of IGF-1Ec by injured tissues, such as by the surrounding tissues in prostate cancer, is reminiscent of the preferential expression of IGF-1Ec post-skeletal muscle damage and that of the myocardium during the post-infarction period. [30][31][32][33][34][35][36] Interestingly, species-specific differences of hEc and mE actions may point to a possible different mode of actions at the receptor level. It has been reported that mE requires IGF-1R for its bioactivity, 36 while hEc appears to act in an IGF-1R independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the major source of circulating IGF-1, producing approximately 75% of plasma IGF-1 (30). IGF-1 is also produced locally by bone cells such as osteoblasts, chondrocytes, osteo-clasts, and osteocytes, thereby functioning as an autocrine/ paracrine effector to regulate bone turnover (19,21,24,30,31). In addition, an inactive form of IGF-1 is stored within the bone matrix, and is activated and released during osteoclastmediated bone resorption (18).…”
Section: The Role Of Igf In Normal Bone Development and Remodelingmentioning
confidence: 99%
“…IGF-1 has an essential role in the development of the growing skeleton and in the maintenance of bone mass during late adulthood and aging. 115 Its mitogenic action selectively promotes cell multiplication in young differentiated clones. 116 It can also stimulate tissue growth and has an important role in bone mass maintenance and acquisition.…”
Section: Gfs In Prpmentioning
confidence: 99%